TRANSFORMASI PEMASARAN TRADISIONAL KE E-MARKETING: TINJAUAN LITERATUR TENTANG DAMPAK PENGGUNAAN TEKNOLOGI DIGITAL TERHADAP DAYA SAING PEMASARAN BISNIS - Istiqomah, Nur Hidayatul (Jurnal Ekonomi Syariah Darussalam, 2023)
This research is a literature review aimed at describing the impact of the transformation from traditional marketing to E-Marketing, with a focus on the use of digital technology on business marketing competitiveness. Through the method of literature review, this research collected and analyzed various sources of literature from scientific journals, books, articles, and research reports related to the topic. The results of the literature review show that digital technology has influenced the way businesses interact with consumers and how companies manage marketing information. The use of social media, websites, and mobile applications has enabled companies to reach consumers more efficiently and effectively. Analytical technology and big data have also provided valuable insights into consumer behavior, allowing companies to develop targeted and personalized marketing strategies. However, this research also reveals that the transformation to E-Marketing also brings challenges. Competition in the digital world is increasingly fierce, forcing companies to innovate continuously to differentiate themselves from competitors and attract consumer interest. Additionally, privacy and data security issues have become critical, and companies must take proactive steps to protect consumer data and build strong trust.